Characteristics of the offer of health services on first level of care in tuberculosis control strategies. DIRESA Callao, 2017 - Reyes Puma, Nora (2019)
Introduction: The constitutional province of Callao is one of the most affected by the epidemic of tuberculosis nationwide. Likewise, it should be considered that the first level health care services are usually the gateway for these patients to the health system. Objectives: To describe the characteristics of the offer of health services in tuberculosis units from first level of care in the Constitutional Province of Callao. Methods: A descriptive study was carried out in 45 tuberculosis units from primary care health services, which investigated the characteristics of infrastructure, human resources and data entry to the information system. Results: 45 primary care health services have “Differentiated units of TB care”; which have 19 doctors, 35 nurses, 3 nutritionists, 10 psychologists, 9 social workers and 50 nursing technicians. 96% of professionals refers doing non-exclusive activities for caring TB patients. 33% have less than 6 months in this work and only 40% have received specific training. In addition, the program’s information system is manual using paper record books. Conclusions: The health services have adequate infrastructure, but there are serious limitations of professionals and information system.